(untitled) (Interdisciplinary Studies Journal, 2026)
This research investigated how the implementation of Educational Robotics, as a practice linked to the maker culture, in Mathematics classes can contribute to the development of the reflective teacher and to the redefinition of their pedagogical practice from the perspective of praxis. The methodological approach was qualitative, grounded in narrative inquiry with a reflective focus. Data were collected through a reflective portfolio. The analysis was conducted using Discursive Textual Analysis (DTA), allowing the identification of robotics’ effects as a catalyst for student engagement and a driver of critical reflections by the teacher-researcher on planning, assessment, and pedagogical mediation. The adoption of formative assessment proved to be fundamental in reorganizing teaching and continuously monitoring learning. The reflective process, nourished by practice and documentation, supported the construction of a more conscious, intentional praxis aligned with the school context. It is concluded that Educational Robotics can expand methodological possibilities in Mathematics teaching and strengthen an investigative and transformative stance by the teacher in the face of contemporary educational challenges.